Klasifikasi data dengan kategori Siswa dan siswi BARU dengan algoritma K-MEANS CLUSTERING - Leni Mawarni Halawa (Interaksi : Jurnal Informatika Dan Teknologi Sistem Informasi, 2025)
Abstract− Students are an input component in the education system that has a big influence on school identity, students are a prioritized component in the education process, so that they become quality human beings in accordance with national education goals (Budi Sutedjo et al. 2010). In the teaching and learning process there are categories of students, especially new students. This category is given to students based on the activities or values obtained during the teaching and learning process.